Chemical composition, antimicrobial, and antioxidant activities of orange essential oil and its concentrated oils. Issue 1 (2nd January 2017) - Torres-Alvarez, C.; Núñez González, A.; Rodríguez, J.; Castillo, S.; Leos-Rivas, C.; Báez-González, J. G.
ABSTRACT: In this study, the chemical composition, antimicrobial, and antioxidant activities of orange essential oil (AN), its folded orange oils (5×, 10×, 20×) and d-limonene (LN) were investigated. The results observed in the chemical composition showed a decrease in the major component LN, in contrast to other minor components, which increased their concentration, such as decanal, linalool, and α-terpineol. The antimicrobial activity was determined for foodborne pathogens using the disk diffusion method followed by the minimum inhibitory concentration and minimum bactericidal concentration. Results showed that folded orange oils (5×, 10×, 20×) had better antimicrobial activity than AN and LN. The antioxidant activity was carried out by 2, 2ʹ-azinobis-3-ethylbenzthiazoline-6-sulphonate and 1, 1-diphenyl-2-picrylhydrazyl methods; folded orange oil 20× presented significantly better results ( p  ≤ 0.05) than other oils studied. Using folded oils from AN could be a natural alternative in food processing as ingredients with antimicrobial and antioxidant effect.